Factors associated with treatment adherence of Brazilian patients undergoing hemodialysis - Nakao, Renata Tamie (2016)
Objective: To evaluate patients’ adherence to hemodialysis (HD) and its relationship to psychosocial variables. Methods: Participated in the study 64 adult patients undergoing HD, assessed in regard to depression, anxiety, social support, disease and treatment knowledge, and adherence. Results: It was found association between sex and adherence to HD, to diet and to medication, as well as between schooling and overall adherence. There is association between disease knowledge and depression, with adherence to fluid restrictions. No association was found between adherence and anxiety. Conclusion: Identifying the determinants of treatment adherence is essential to devise efficacious strategies to improve patients’ quality of life.